Homeland Security, Homeland Defense and Clarifying Northern Command's Maritime Security Role - Kelly, William R. (2004)
This paper seeks to explore the relationship between the Department of Defense's Homeland Defense role and the Department of Homeland Security's Homeland Security role. It compares the two at the policy level and reviews definitions, nomenclature and applicability, using the Maritime Homeland Security subset as the backdrop against which to examine issues. Additionally, it explores the relationship between NORTHCOM, the Joint Forces Maritime Component Commander and the Department of homeland Security and the U.S. Coast Guard. It provides suggestions to resolve coordination and effort overlap issues and offers a notional Joint Operations framework to coordinate the future efforts of all levels of government as they carry out their responsibilities to proved both defense and security fore the Homeland. The original document contains color images.